Intergenerational effects of dietary changes on trait means and variance - Lee, Marcus ; 0000-0002-3320-3010; Tran, Kevin; Castillo, Yasmine; Walsh, Matthew R. (Biology letters, 2025)
Environmental stress can alter not only trait means but also trait variances - an often-overlooked evolvable feature with ecological and evolutionary relevance. We examine how dietary stress affects both the mean and variance of morphological and reproductive traits across two generations in clonal Daphnia. We manipulated maternal and offspring environments with high- (algae) or low-quality (cyanobacteria) diets, measuring eye size, body size and reproductive output in eight genotypes. Morphological trait means showed consistent treatment-by-generation interactions: low-quality diets reduced trait size, with partial recovery upon re-exposure to high-quality food. Reproduction was largely determined by current conditions, while eye and body size showed legacy effects of maternal environment. Variance patterns were trait-specific: eye size variance declined under stress, body size variance increased across generations and reproductive variance peaked in offspring released from maternal stress. We developed a conceptual framework considering roles for condition transfer, anticipatory plasticity and diversified bet-hedging as potential mechanisms underlying these intergenerational impacts on trait variances. Although no single mechanism explained all outcomes, our findings tentatively support condition transfer and suggest potential co-occurrence of multiple strategies. This study underscores the importance of jointly examining mean and variance responses to stress to better understand phenotypic plasticity and its evolutionary consequences.
Keywords: developmental plasticity; environmental canalization; maternal effects; trait variability; zooplankton